Zooplankton Community in The Waters of Lab Faculty of Fisheries and Marine Science East Likupang North Minahasa - Marlinda R. Malara; Gaspar D. Manu; Ruddy D. Moningkey (Jurnal Ilmiah PLATAX, 2020)
The purpose of this study was to determine the type, density, and community structure of the Zooplankton including the Diversity Index (H '), Dominance Index (C), and Evenness (e). Sampling was carried out on November 12, 2019, using planktonet to a depth of 10 m from sea level, and carried out vertically as much as 3 times at each sampling point. The results obtained were 22 genus 26 species in 3 classes, namely: Paracalanus sp, Rhincalanus sp, Calanus sp., Corycaeus sp., Acrocalanus sp., Oncaea sp., Oithona sp., Scolecithricella sp., Euterpina sp., Eurytemora sp., Centropages sp., Ctenocalanus sp., Eucalanus sp., Pseudocalanus sp., Microsetella sp., Nauplius sp., Squilla sp., Siriella sp., Pseudeuphausia sp., Nematocelis sp., Zoea., Solenocera sp. The highest relative density was found in Paracalanus sp which was 39.38%. The Diversity (H ') of zooplankton at two sampling points is classified as moderate. These values indicate the community of planktonic organisms in the areas of study is less diverse. And Dominance Index (C) shows that no species dominates the waters of East Likupang.Keywords: Community; Zooplankton; East Likupang; Domination; Diversity.AbstrakTujuan penelitian ini adalah untuk mengetahui jenis, kepadatan, dan  struktur komunitas Zooplankton seperti Indeks Keanekaragaman (H’), Indeks Dominansi (C), dan Keseragaman (e). Pengambilan sampel dilakukan pada 12 November 2019 mengunakan planktonet sampai kedalaman 10 m dari permukaan laut, dilakukan secara vertikal sebanyak 3 kali pada setiap titik. Berdasarkan hasil pengamatan diperoleh 22 genus 26 spesies dalam 3 kelas yaitu : Paracalanus sp, Rhincalanus sp, Calanus sp., Corycaeus sp,  Acrocalanus sp., Oncaea sp, Oithona sp., Scolecithricella sp., Euterpina sp., Eurytemora sp., Centropages sp., Ctenocalanus sp., Eucalanus sp., Pseudocalanus sp., Microsetella sp., Nauplius sp., Squilla sp., Siriella sp., Pseudeuphausia sp., Nematocelis sp., Zoea., Solenocera sp. Kepadatan Relatif tertinggi terdapat pada Paracalanus sp yakni 39.38%. Keanekaragaman (H’) zooplankton di dua titik tergolong sedang. Nilai tersebut menunjukkan komunitas organisme dalam kondisi yang kurang beragam. Dan Dominansi (C) menunjukkan tidak ada spesies yang mendominasi di perairan Likupang Timur.Kata kunci: Komunitas; Zooplankton; Likupang Timur; Dominasi; Keanekaragaman.